2022
DOI: 10.12998/wjcc.v10.i10.3206
|View full text |Cite
|
Sign up to set email alerts
|

Myomatous erythrocytosis syndrome: A case report

Abstract: BACKGROUND Uterine myoma is the most common benign tumor among women and is often accompanied by anemia. Here, we report the case of a patient with a very large leiomyoma but with a hemoglobin level as high as 197 g/L. After undergoing hysterectomy, all her hematological parameters returned to normal. Immunohistochemical staining of her myoma for erythropoietin showed strong positivity, which suggested that erythropoietin may be the cause of her erythrocytosis. A multidisciplinary team played a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Traditionally, MES is diagnosed by immunostaining for EPO. 16 Although pathologic sampling and staining were not conducted in this case, the researchers believe that a diagnosis of MES is warranted because the patient's laboratory values significantly dropped following UAE and remained at baseline following the removal of her uterus. It is important to note that this patient was on an oral contraceptive pill, which can increase the risk of VTE and stroke; therefore, OCP (Oral Contraceptive Pill) use must be considered as a possible cofounder.…”
Section: Discussionmentioning
confidence: 92%
“…Traditionally, MES is diagnosed by immunostaining for EPO. 16 Although pathologic sampling and staining were not conducted in this case, the researchers believe that a diagnosis of MES is warranted because the patient's laboratory values significantly dropped following UAE and remained at baseline following the removal of her uterus. It is important to note that this patient was on an oral contraceptive pill, which can increase the risk of VTE and stroke; therefore, OCP (Oral Contraceptive Pill) use must be considered as a possible cofounder.…”
Section: Discussionmentioning
confidence: 92%
“…Evidence supports an increase in EPO levels in MES cases [5,9]. However, from the literature review of Mui et al [5], the presence of hydronephrosis was not different among MES cases, as well as clinical dyspnea or hypoxia was not always seen [2,10]. In addition, this makes this theory less reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Suresh and Rizk [9] discovered positivity of EPO immunohistochemistry in fibroid tissue, and the authors detected an increase in EPO level in blood serum, which returned to normal levels after removal of the mass. Moreover, Shu et al [10] found that EPO immunohistochemical staining was strongly positive in the myoma tissue, which may be the cause of erythrocytosis. This led to the hypothesis that EPO production from fibroids is responsible for MES.…”
Section: Discussionmentioning
confidence: 99%